1990
DOI: 10.1088/0953-2048/3/5/009
|View full text |Cite
|
Sign up to set email alerts
|

The possibility of using high-Tcsuperconducting films as elements of a rectifier

Abstract: The use of a high-T, YBaCuO superconducting film as a switch element of a rectifier was investigated. It was shown that a film can work as a controlled switch at a frequency up to 20 Hz, at current "4 A and voltage "4 V with current-stimulated quench. Film performance in the switch mode was calculated and theories and experiments were compared. Based on high-T, films it is possible to develop superconducting rectifiers that can work at the temperature of liquid nitrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…It was shown recently in Mataira et al [7,8] that the open-circuit voltage can be explained well -most importantly, with good quantitative agreement -using classical electromagnetic theory. The DC output voltage obtained from an HTS dynamo arises naturally from a local rectification effect caused by overcritical eddy currents [7][8][9][10][11][12]: an effect that has been observed in HTS materials as far back as Vysotsky et al [13]. The gap dependence of the open-circuit voltage computed by Ghabeli and Pardo [14] also agrees with experiments.…”
Section: Introductionsupporting
confidence: 71%
“…It was shown recently in Mataira et al [7,8] that the open-circuit voltage can be explained well -most importantly, with good quantitative agreement -using classical electromagnetic theory. The DC output voltage obtained from an HTS dynamo arises naturally from a local rectification effect caused by overcritical eddy currents [7][8][9][10][11][12]: an effect that has been observed in HTS materials as far back as Vysotsky et al [13]. The gap dependence of the open-circuit voltage computed by Ghabeli and Pardo [14] also agrees with experiments.…”
Section: Introductionsupporting
confidence: 71%
“…It was shown recently in Mataira et al [14,15] that the behaviour of the HTS dynamo can be explained well-most importantly, with good quantitative agreement-using classical electromagnetic theory. The DC output voltage obtained from an HTS dynamo arises naturally from a local rectification effect caused by overcritical eddy currents flowing within the HTS wire [6-8, 14, 16]: a classical effect that has been observed in HTS materials as far back as Vysotsky et al [17]. The gap dependence of the open-circuit voltage computed by Ghabeli and Pardo [18] also agrees with experiments.…”
Section: Introductionmentioning
confidence: 60%
“… n E (16) This gives a solution where the flux of the magnet is completely enclosed in the rotor domain and H = 0 elsewhere. By the principle of superposition, it must be the case that the field of the PM is contained inside the boundary ∂Ω R by a shell current, K shell , on this boundary, that produces the opposite PM field outside the boundary, i.e., H m + H shell = 0.…”
Section: H-formulation + Shell Current (H+sc)mentioning
confidence: 99%
“…This approach does not rely on a separate rectifying 'switch' component which simplifies the architecture of transformerdriven LTS flux pumps. In later work, Vyssotsky et al [50] proposed using HTS thin film as the switching element in a similar type of device, through exploiting the highly nonlinear E-J resistivity of these materials [51]. Subsequently, Geng et al [52] have demonstrated this approach, in an HTS self-rectifier which used a coated conductor wire as a noninductive bridge, and was capable of delivering a maximum ouput current of ∼80 A.…”
Section: Introductionmentioning
confidence: 99%